Analisis Penjatuhan Pidana di Bawah Ancaman Minimum Tindak Pidana Narkotika dalam Asas Legalitas dan Kemandirian Hakim : Studi Putusan Nomor 7853/K/Pid.Sus/2024 (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the juridical issues related to the implementation of criminal sanctions below the statutory minimum, as reflected in Cassation Decision Number 7853/K/Pid.Sus/2024. The focus of this research centers on the tension between the rigid provisions of Article 111 paragraph (1) of Law No. 35 of 2009 concerning narcotics and the reality of judicial practice, which often deviates from these provisions. This phenomenon raises debates regarding the extent to which the principle of legality can be compromised in pursuit of justice without undermining the pillar of legal certainty within Indonesia’s criminal justice system. Using a normative legal research method with a statutory and case study approach, this study qualitatively analyzes judges’ considerations. The findings indicate that, although the policy of imposing sentences below the minimum carries the risk of creating legal uncertainty, the Supreme Court in this case reinterpreted the principle of legality. Judges tend to prioritize proportionality and substantive justice to avoid purely mechanical punishment. The study concludes that, while judicial discretion represents a concrete expression of judicial independence, such practice requires clearer normative parameters. Without explicit regulation, deviations from the statutory minimum risk widening disparities in judicial decisions. Therefore, standardized sentencing guidelines are necessary to preserve legal integrity while maintaining a sense of justice for defendants.